Klasifikasi dan Rekomendasi Aspek Kelembagaan Pusat Pelatihan Pertanian Perdesaan Swadaya (P4S) di Provinsi Kalimantan Selatan - Retno Hermawan (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2020)
This research is an evaluation research on P4S ability class. P4S capability classes are rated through 5 components; (a) Learning Infrastructure, (b) Institutional, (c) Organizing Training / Commerce, (d) Manpower, and (e) Agribusiness Business Development. The purpose of this paper is to know P4S institutional ability classes, and provide recommendations for improving aspects of P4S ability classes. Purposive sampling method with descriptive data analysis. When the study was conducted from March 6 to May 15, 2020. The results showed that there were 5 Beginner Classes, 13 Associate Classes and 2 Main Classes. P4S South Kalimantan region needs to be improved in aspects a) Institutional, related to the job description of management and AD ART, b) Organizing Training / Apprenticeship, training material has not been physically proven and low frequency & intensity of organizing training / apprenticeship, c) Agribusiness Business Development, it is necessary to foster increased agricultural production in order to be able to export, increase business networks with entrepreneurs and increase training networks so that they can work together with educational institutions and other stakeholders.